Quality of Discharge Education: Chronic Diseases Patients’ Perspectives - Rahmawati, Syifa Eka; Kurniawan, Titis; Sari, Eka Afrima; Trisyani, Mira; Pahria, Tuti (Indonesian Journal of Global Health Research, 2024)
Readmission is a condition where a patient needs to be re-hospitalized shortly after their initial discharge. One crucial component in preventing readmission is the quality of discharge education. Objective: This study aims to describe the quality of discharge education among patients with chronic diseases Method : A quantitative descriptive study design was used. A total of 121 in patients with chronic disease from a regional general hospital in West Java were selected through consecutive sampling. Demographic and characteristic questionnaires and the Quality of Discharge Teaching Scale (QDTS) were used as instruments. It consisting of 6 paired questions with a validity value 0.98 and reliability 0.92. Descriptive statistics were applied for data analysis. Results: Chronic patients' score of content needed and content received were high (46.7 ± 11.9). This means that patients have high information needs and the information they received from nurses answer their needs. However, there are some points where it is considered that the needed information has not been fulfilled by the information received. Conclusions: Even though the quality of the provided discharge education is high, the improvement particularly in terms of information related to who and when should be contacted and information about emotion are needed.